A Comparison of Endotracheal Intubation Success Using Video Laryngoscopy and Reconstructed Laryngoscopes Among Health Workers in Nusa Penida - Tethool, Heinz Fernando; Parami, Pontisomaya; Chandra, Steven (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif, 2025)
Background: Endotracheal intubation is a critical procedure in the management of patients with respiratory distress. The two main methods used are video laryngoscopy and reconstructive laryngoscopy. This study aims to compare the duration and number of intubation attempts using video laryngoscopy and reconstructed laryngoscopy in health workers in Nusa Penida.Objective: This study aimed to compare the time and number of endotracheal intubations performed by healthcare workers in Nusa Penida using two strategies, video laryngoscopy and repeat laryngoscopy. The study involved healthcare specialists who performed intubations in the model, with two groups of 31 people each.Methods: This study used a quasi-experimental design involving health workers in Nusa Penida who performed endotracheal intubation using a video laryngoscope and a reconstructed laryngoscope on mannequins. Two groups of 31 samples were created for the study, and both were given intubation training using a laryngoscope video and direct laryngoscopy.Results: The outcomes of this study were the duration of intubation and the number of attempts required by each respondent to intubate successfully after training. The study used statistical analysis to compare outcomes, employing a paired t-test. The results indicated that the average duration of intubation using laryngoscopy was 31.7 seconds (range: 13 - 93 seconds), while video laryngoscopy took 22.9 seconds (range: 11-49 seconds), with a significance level of P < 0.014. Additionally, the average number of intubation trials was 1.29 (range: 1 - 3) for direct laryngoscopy and 1.03 (range: 1 - 2) for video laryngoscopy, with a significance level of P < 0.018.Conclusion: There is a difference in the use of the video laryngoscope better in terms of duration and intubation attempts.